Peripheral tissue oxygenation during standard CPB and miniaturized CPB (direct oxymetric tissue perfusion monitoring study) - Manďák, Jiří; Brzek, Vladimír; Svitek, Vladimír; Děrgel, Martin; Chek, James Lago; Volt, Martin; Horák, Miroslav; Kubíček, Jaroslav; Lonský, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2013)
AIM: The aim of this study was to compare the impact of standard cardiopulmonary bypass (CPB) with mini CPB on peripheral tissue perfusion. METHODS: 24 patients with ischemic heart disease scheduled for CPB were randomised to two groups: Group A (12 patients, standard CPB) and Group B (12 patients, mini CPB). Oxygen tension was measured with an optical multiparametric sensor inserted into the patient's deltoid muscle. RESULTS: Lower priming in Group B (870 ± 221 mL) vs. Group A (1502 ± 48 mL) and significantly reduced hemodilution during mini CPB (Group B 25.3 ± 1.1% vs. Group A 30.1 ± 2.3%) were recorded. Higher and continuous blood flow during perfusion was analysed in Group A (4.58 ± 0.34 L.min(-1)) and lower than calculated blood flow was found in Group B (3.49 ± 0.51 L.min(-1) vs. 4.66 ± 0.38 L.min(-1)). There was a direct correlation between mean arterial pressure (MAP) and ptO2 in Group A during CPB and a direct correlation between pump blood flow and MAP during CPB in Group B. Higher levels of ptO2 during CPB and surgery after CPB in comparison with initial levels were found in Group B. Decreased ptO2 levels after surgery were found in both groups. CONCLUSION: Mini CPB enables perfusion with a relatively low flow. The results of this study suggest that a flow decrease in mini CPB is well tolerated by the organism.
Keywords: vzorkové studie; oxymetrie; mikrocirkulace; Sampling Studies; hodnocení rizik; Female; Myocardial Ischemia; ženské pohlaví; Reproducibility of Results; musculus deltoideus; Deltoid Muscle; Oxygen Consumption; kardiopulmonální bypass; lidé; Elective Surgical Procedures; Pilot Projects; ischemická choroba srdeční; Oximetry; pilotní projekty; Risk Assessment; Cardiopulmonary Bypass; Risk Factors; reprodukovatelnost výsledků; Male; Aged; Oxygen; Microcirculation; rizikové faktory; lidé středního věku; Arterial Pressure; elektivní chirurgické výkony; senioři; mužské pohlaví; arteriální tlak; Middle Aged; kyslík; spotřeba kyslíku; Humans